Prosedur Pencairan dan Penerimaan Alokasi Dana Desa (ADD) untuk Pembangunan Nagari Tabek Panjang Kecamatan Baso Kabupaten Agam - Sabri, Sabri; Febrianti, Eka; Asnah, Asnah; Nasfi, Nasfi (Jurusan PIPS FKIP UMMY Solok, 2019)
The purpose of this study was to determine the procedure for disbursing village fund allocations and how to receive village fund allocation (ADD) in the 2018 fiscal year at Nagari Tabek Panjang, Baso District. This research is located in Nagari Tabek Panjang, Baso District, Agam Regency, West Sumatra Province. The type of data used is qualitative data. Data collection was carried out by means of interviews and documentation by determining the parties who became the resource persons. The results showed that the Village Fund Allocation (ADD) disbursement procedure was carried out in stages namely stages I, II, III. For disbursement in the first phase after the Nagari Regulation on ABPNag 2018 was approved by the Agam Regency Nagari Community Empowerment Agency (DPMN) verification team, and for the second stage disbursement must report accountability to the Agam Regency DPMN. In the ADD Acceptance Process, the Nagari RPJM was compiled, the Nagari RKP Compilation and Determination, and the Nagari Expenditure Budget (APBNAg) Long Term Budgeting Budget Compilation 2018